Bacterial Cell Growth Inhibitors Targeting Undecaprenyl Diphosphate Synthase and Undecaprenyl Diphosphate Phosphatase. (31st August 2016) - Wang, Yang; Desai, Janish; Zhang, Yonghui; Malwal, Satish R.; Shin, Christopher J.; Feng, Xinxin; Sun, Hong; Liu, Guizhi; Guo, Rey‐Ting; Oldfield, Eric
Abstract: We synthesized a series of benzoic acids and phenylphosphonic acids and investigated their effects on the growth of Staphylococcus aureus and Bacillus subtilis . One of the most active compounds, 5‐fluoro‐2‐(3‐(octyloxy)benzamido)benzoic acid (7, ED50 ∼0.15 μg mL −1 ) acted synergistically with seven antibiotics known to target bacterial cell‐wall biosynthesis (a fractional inhibitory concentration index (FICI) of ∼0.35, on average) but had indifferent effects in combinations with six non‐cell‐wall biosynthesis inhibitors (average FICI∼1.45). The most active compounds were found to inhibit two enzymes involved in isoprenoid/bacterial cell‐wall biosynthesis: undecaprenyl diphosphate synthase (UPPS) and undecaprenyl diphosphate phosphatase (UPPP), but not farnesyl diphosphate synthase, and there were good correlations between bacterial cell growth inhibition, UPPS inhibition, and UPPP inhibition. Abstract : UPP ‐ward antibiotic trends : We synthesized 30 benzoic and phenylphosphonic acids and discovered several that inhibit Staphylococcus aureus and Bacillus subtilis growth. They act synergistically with antibiotics that target cell‐wall biosynthesis but not with other antibiotics. The most potent compounds were found to target undecaprenyl diphosphate phosphatase (UPPP) and undecaprenyl diphosphate synthase (UPPS), and there were good correlations between enzyme and cell growth inhibition.